PHYSIOLOGICAL FOUNDATIONS OF THE NERVOUS SYSTEM AND ITS ROLE IN THE REGULATION OF VITAL PROCESSES OF THE HUMAN BODY - Mo’minov M.Sh, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The  nervous  system  is  one  of  the  most  important  regulatory  systems  in  the human body, coordinating the activity of all organs and physiological systems. This article provides a detailed analysis of the physiological characteristics of the nervous system, the structure and functions of nerve cells, and the mechanisms underlying the generation  and  transmission  of  nerve  impulses.  The  functional  interrelationship between the central and peripheral nervous systems, the physiological basis of reflex activity,  and  the  influence  of  the  autonomic  nervous  system  on  the  regulation  of internal organ functions are discussed based on scientific evidence. In addition, the clinical significance of nervous system physiology is examined, particularly  the  role  of  nervous  system  dysfunction  in  the  development  of  various neurological  and  psychosomatic  disorders.  The  article  also  highlights  the  positive effects of a healthy lifestyle, stress management, adequate sleep, and physical activity on  nervous  system  function,  with  preventive  aspects  substantiated  from  a  medical perspective.